2022
DOI: 10.1126/science.abp9466
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of nucleosome disassembly and reassembly by RNAPII elongation complex with FACT

Abstract: During gene transcription, RNA polymerase II (RNAPII) traverses nucleosomes in chromatin, but its mechanism has remained elusive. Using cryo-electron microscopy, we obtained structures of the RNAPII elongation complex (EC) passing through a nucleosome, in the presence of transcription elongation factors Spt6, Spn1, Elf1, Spt4/5, and Paf1C and the histone chaperone FACT. The structures show snapshots of EC progression on DNA, mediating downstream nucleosome disassembly followed by its reassembly upstream of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
74
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 93 publications
2
74
2
Order By: Relevance
“…While the nucleosome represents the major histone-DNA assembly in cellular chromatin, histone-DNA complexes with alternative stoichiometries, such as subnucleosomes, have also been observed ( 5 , 6 ). For example, the hexasome, which has one less H2A-H2B dimer than the canonical nucleosome, can form when the transcription machinery traverses a nucleosome during elongation ( 7 , 8 ). Indeed, hexasomes are detected throughout the genome ( 9 , 10 ).…”
mentioning
confidence: 99%
“…While the nucleosome represents the major histone-DNA assembly in cellular chromatin, histone-DNA complexes with alternative stoichiometries, such as subnucleosomes, have also been observed ( 5 , 6 ). For example, the hexasome, which has one less H2A-H2B dimer than the canonical nucleosome, can form when the transcription machinery traverses a nucleosome during elongation ( 7 , 8 ). Indeed, hexasomes are detected throughout the genome ( 9 , 10 ).…”
mentioning
confidence: 99%
“…Spt4/5 (DSIF for mammals) is one of the transcription elongation factors that is tightly associated with transcribing RNAPII 39 , 40 . It binds and seals the RNAPII DNA-binding cleft 41 , and enhances the transcription elongation efficiency in the nucleosome 35 , 41 43 . Interestingly, when the Spt4/5-bound RNAPII structure was superimposed on the current RNAPII-chromatosome complex, Spt4/5 overlapped with the exit linker DNA in the form I complex (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A recent structure of the yeast RNAP2 elongation complex revealed that the Spn1 TND preceded by HEAT subdomain is recruited to RNAP2 through association with the Spt5 NGN and KOW2 domains using an interface distinct from the one needed for association with TIMs, leaving the TIM binding site open for interaction with Spt6 [ 49 ]. Importantly, the IWS1-TND:SPT6-TIM interaction interface in the context of fully assembled elongation complexes and RNAP2 is structurally similar to the binary complex resolved by protein NMR or crystallography [ 6 , 21 , 22 , 49 ], confirming that the binary TND:TIM interactions exist in the context of larger assembled complexes.…”
Section: Transcriptional Roles Of Tnd Across Proteins and Speciesmentioning
confidence: 99%